A Book Review of Problem-Based Learning in Elementary School: Strategies for What Helps Students Thrive - Imellia Imellia; Duano Sapta Nusantara; Da Tien Nguyen; Rohati Rohati (MASI Mandiri Edukasi, 2026)
This book review examines Problem-Based Learning in Elementary School: Strategies for What Helps Students Thrive by Samantha S. Reed, Carol A. Mullen, and Emily T. Boyles. The book discusses the implementation of problem-based learning (PBL) as an instructional approach that supports students’ knowledge and skill development through collaborative engagement in solving authentic, real-world problems. This review adopts a descriptive-critical approach, analyzing the book’s content, theoretical foundation, key themes, and findings from teacher interviews, while also evaluating its relevance to classroom practice in elementary education. The book emphasizes the development of 21st-century skills, known as the 5Cs, namely critical thinking, creativity, communication, collaboration, and citizenship, and demonstrates how PBL can enhance student engagement, motivation, and academic achievement. Its main strength lies in bridging PBL theory with classroom practice through teachers’ lived experiences, making it highly relevant for educators and education stakeholders. However, the book has limitations, particularly in its limited discussion of assessment practices, teacher training, scaffolding strategies, and the challenges of implementing PBL across diverse educational contexts, indicating the need for further elaboration to strengthen its practical applicability.